2021
DOI: 10.1002/dev.22095
|View full text |Cite
|
Sign up to set email alerts
|

Gene x responsive parenting interactions in social development: Characterizing heterogeneity in autism spectrum disorder

Abstract: Emerging research suggests that caregiving environments and genetic variants independently contribute to social functioning in children with typical development or autism spectrum disorder (ASD). However, biologically plausible interactive models and complimentary assessment of mechanisms are needed to: (a) explain considerable social heterogeneity, (b) resolve inconsistencies in the literature, and (c) develop and select optimal treatments based on individual differences. This study examined the role of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…They found that children with 'susceptibility markers' (dopamine and serotonin-related gene polymorphisms) were more strongly influenced by parenting behaviours, indicated by a significant moderation of the association between responsive parenting behaviours and children's social skills (Caplan et al, 2021). Although these 'susceptibility markers' were the same as in non-autistic populations (e.g., Bakermans-Kranenburg & van IJzendoorn, 2011;van IJzendoorn et al, 2012), they have also been associated with autism and environmental susceptibility within autism (e.g., Reiersen & Todorov, 2011;Wiggins et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that children with 'susceptibility markers' (dopamine and serotonin-related gene polymorphisms) were more strongly influenced by parenting behaviours, indicated by a significant moderation of the association between responsive parenting behaviours and children's social skills (Caplan et al, 2021). Although these 'susceptibility markers' were the same as in non-autistic populations (e.g., Bakermans-Kranenburg & van IJzendoorn, 2011;van IJzendoorn et al, 2012), they have also been associated with autism and environmental susceptibility within autism (e.g., Reiersen & Todorov, 2011;Wiggins et al, 2014).…”
mentioning
confidence: 99%
“…Moreover, as some children at EL of autism may be especially susceptible to parenting behaviours (e.g., Caplan et al, 2021, van IJzendoorn & Bakermans-Kranenburg, 2015, this investigation could provide a better understanding of the individual strengths and vulnerabilities in this specific population and open windows for tailored intervention.…”
mentioning
confidence: 99%